Arquitetura de um provedor de serviços interativos para sistemas de televisão digital - Prado, Gabriel Massote (Universidade Federal de São Carlos, 2011)
The evolution of television systems, analog to digital, provides a wide range of new services possibility of data transmission from the high quality audio and video. With the aggregation of data transmission of television programs, systems arise Interactive Digital TV allows you to embed interactive content resulting in a new way to produce and transmit television programs. This paper presents an architecture of an Interactive Service Provider named Interactive Service Provider for Digital Television Systems - ispTV - to interactive digital television systems, based on a service-oriented architecture that enables the publication and delivery of services in different technologies such as JAX-WS, Axis2 and ispTV services, with the inclusion of an abstract layer of communication in order to simplify the development of interactive programs with a standardized communication APIs provided by the architecture. The Brazilian Digital Television System is to provide an objective of social, cultural and technological inclusion through broadcasting educational, government and commercial television applications for the television user programs. In this context, this paper presents some interactive applications with educational support to viewers with special needs using the proposed architecture. The applications presented demonstrate the usability aspects of the architecture along ispTV to test usability of the APIs of abstraction that the architecture offers. Also presented are performance testing and scalability of the architecture, showing that its operation allows its use for the transmission of interactive applications for various classes of projects, institutions and companies.
Keywords: Software - desenvolvimento; Televisão digital; Serviços da WEB; Televisão Digital Interativa; Canal de Interatividade; Middleware; Ginga; Brazilian System of Digital Television; Interactive Television; Interactive Channel; Ginga; Web service; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO